School-Based Mental Health Services: Disparities for Youth with ASD - Ringgold, Alicia (East Carolina University, 2023)
As children’s mental health needs are increasing across the United States, mental health treatment services are becoming more readily available. School-based mental health services (SBMHS) are widely accepted as an efficient and effective way to deliver mental health services to students, but youth with Autism Spectrum Disorder (ASD) are continuously overlooked in these programs (Dickson et al., 2021). In order to better understand the disparities in delivering SBMHS to students with ASD, we have developed a survey for the teachers, administrators, and student support staff in two counties in Eastern North Carolina. This survey will assess their knowledge of mental health needs of students with ASD and their willingness to participate in training about mental health conditions and services in this population.
Keywords: Autism Spectrum Disorder; Mental Health; School Services